2012
DOI: 10.1371/journal.pbio.1001416
|View full text |Cite
|
Sign up to set email alerts
|

Differential Age-Dependent Import Regulation by Signal Peptides

Abstract: The import of certain proteins into chloroplasts is dependent on the age of the organelle, with age-dependent import being controlled by a specific motif within the signal peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 50 publications
5
62
0
Order By: Relevance
“…For example, cpHsc70 interacts with the N-terminal motif of TPs, which has a moderate hydrophobicity conferred by a few hydrophobic amino acids (Lee et al, 2008;Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015). A recent study by Teng et al (2012) also supports this notion; they showed that preproteins with two consecutive basic residues are actively imported into older chloroplasts, whereas those with two consecutive acidic residues are not. The two mechanisms may not be mutually exclusive, but are utilized depending on the situation or the specific translocon component(s) involved.…”
Section: Discussionmentioning
confidence: 90%
“…For example, cpHsc70 interacts with the N-terminal motif of TPs, which has a moderate hydrophobicity conferred by a few hydrophobic amino acids (Lee et al, 2008;Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015). A recent study by Teng et al (2012) also supports this notion; they showed that preproteins with two consecutive basic residues are actively imported into older chloroplasts, whereas those with two consecutive acidic residues are not. The two mechanisms may not be mutually exclusive, but are utilized depending on the situation or the specific translocon component(s) involved.…”
Section: Discussionmentioning
confidence: 90%
“…The TPs were clustered into nine groups based on their H70BS patterns within the first 80 aa (TP and part of mature protein sequence) using Hierarchical clustering. These groups show pronounced differences in the position of their highest affinity, which varied from position 5 to 70 (5,10,17,23,32,46,52,58, and 70 for groups 1-9, respectively). This fairly even distribution raised a concern that the H70BS was randomly distributed.…”
Section: Resultsmentioning
confidence: 99%
“…Using a clustering algorithm, we can group these TPs into nine clusters where the position of the strongest H70BS is located in different regions. How this H70BS placement functions in relation to the other identified motifs (15,18) and contributes to a general TP design (21,57,58) will be the subject for further study. It is now clear that only three clusters of the TPs have a strongest H70BS within their N-ter 20 aa and together represent 32% of the TPs.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5B, the RidA-GFP fusion protein was found to localize exclusively to chlorophyll-containing chloroplasts in both guard and mesophyll cells. Notably, in mesophyll cells, the RidA-GFP fusion seemed more abundant in smaller chloroplasts than larger ones ( Figure 5B, lower panel), suggesting that, like certain other chloroplast proteins, the targeting of RidA may be influenced by chloroplast age, import capacity, and/or metabolic activity (Kessler and Schnell, 2009;Teng et al, 2012). The Thr dehydratase-GFP fusion protein also localized exclusively to chloroplasts in Arabidopsis mesophyll cells ( Figure 5C).…”
Section: Rida and Thr Dehydratase Are Plastid-targetedmentioning
confidence: 95%